Nano-selenium and nano-zinc oxide supplementation in syrup on laying area, population size and hsp gene expression of honey bees in hot climate - Amini Esfidvajani, Mohamadbagher; Sadeghi, Ali Asghar; Shawrang, Parvin; Chamani, Mohamad; Aminafshar, Mehdi (Acta Scientiarum. Animal Sciences, 2020)
This study was designed to examine the protective effects of nano-selenium and nano-zinc oxide on queen and workers performance under heat stress condition and gene expression of heat shock protein 70 (hsp70) as an index of heat tolerance. Sixty colonies were randomly assigned to five treatments with 12 replicates from June until early September. Sugar syrup (50%) containing no supplement or nano-selenium at levels of 50 and 100 µg L-1 or nano-zinc at levels of 100 and 200 µg L-1 was fed to colonies. Nano-selenium supplementations had no effect, but nano-zinc at level of 100 µg L-1 significantly decreased body malondialdehyde concentration. The highest bee population was seen in nano-zinc at level of 100 µg L-1 and the lowest one in control group. The lowest and the highest body weight, fat and protein deposition was found in group received nano-zinc at level of 100 µg L-1 and control, respectively. The highest gene expression was for group received nano-zinc at level of 100 µg L-1 In group received nano-zinc at level of 100 µg L-1, an increase in hsp70 gene expression was found. In conclusion, nano-zinc oxide at level of 100 µg L-1 could increase queen and worker performance and heat resistance of bees in the hot climate condition.